2021
DOI: 10.1159/000514018
|View full text |Cite
|
Sign up to set email alerts
|

Towards Modelling Genetic Kidney Diseases with Human Pluripotent Stem Cells

Abstract: <b><i>Background:</i></b> Kidney disease causes major suffering and premature mortality worldwide. With no cure for kidney failure currently available, and with limited options for treatment, there is an urgent need to develop effective pharmaceutical interventions to slow or prevent kidney disease progression. <b><i>Summary:</i></b> In this review, we consider the feasibility of using human pluripotent stem cell-derived kidney tissues, or organoids, to model gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…A key finding from this study is that organoids form BMs early during differentiation, and more importantly, recapitulate a sequence of assembly events with initial deposition of laminin followed by incorporation of collagen IV, nidogen and perlecan (Brown et al, 2017;Sasaki et al, 2004). Kidney organoids have also provided new insights into disease processes (Rooney et al, 2021;Tanigawa et al, 2018;Tian and Lennon, 2019). We found that organoids with a pathological missense variant in COL4A5 differentiated and deposited core BM proteins, including a collagen IV 345 network, which is described in missense variants.…”
Section: Discussionmentioning
confidence: 90%
“…A key finding from this study is that organoids form BMs early during differentiation, and more importantly, recapitulate a sequence of assembly events with initial deposition of laminin followed by incorporation of collagen IV, nidogen and perlecan (Brown et al, 2017;Sasaki et al, 2004). Kidney organoids have also provided new insights into disease processes (Rooney et al, 2021;Tanigawa et al, 2018;Tian and Lennon, 2019). We found that organoids with a pathological missense variant in COL4A5 differentiated and deposited core BM proteins, including a collagen IV 345 network, which is described in missense variants.…”
Section: Discussionmentioning
confidence: 90%
“…We discovered that organoids form BMs early during differentiation, and more importantly, recapitulate a sequence of assembly events with initial deposition of laminin followed by incorporation of type IV collagen, nidogen and perlecan (Brown et al, 2017;Sasaki et al, 2004). Kidney organoids have also provided new insights into developmental programmes and disease processes (Rooney et al, 2021;Tanigawa et al, 2018;Tian and Lennon, 2019). We found that organoids with a pathological missense variant in COL4A5 differentiated and deposited core BM proteins, including a collagen 345 network, which is described in missense variants.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, they have the potential to differentiate into the three germ layers (mesoderm, endoderm and ectoderm) of the early embryo and thus form all organs. As recently reviewed [ 6 , 7 ] and depicted in Fig. 1 , there are two sources of PSCs for research studies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other types of molecule, especially transcription factors and extracellular matrix proteins, were found to be expressed by the developing kidney and were essential for its normal development [13] . Of note, the genes encoding several of these molecules have been found to be mutated in individuals with congenital kidney disease [7] . The UB and MM themselves each originate from separate compartments within the intermediate mesoderm [14] , that itself has formed during gastulation, the name of the event when the three germ layers form early on in embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation